"Art, Space, Mobility in Early Ages of Globalization": A Project, Multiple Dialogue, and Research Program. (31st March 2017) - Baader, Hannah; Shalem, Avinoam; Wolf, Gerhard
Abstract: "Art, Space, Mobility in Early Ages of Globalization" aims to promote a new history of art that recognizes the complex and diverse connections forged between the Mediterranean region, the Middle East, Central Asia, and the Indian subcontinent from the fourth through the sixteenth centuries. Over the past four years, this project has brought together more than one hundred junior scholars from countries around the world, including Georgia, Armenia, Turkey, Tunisia, Romania, Greece, Spain, Mongolia, Israel, India, Italy, the United States, Denmark, Switzerland, Germany, and China, as well as twenty distinguished senior scholars from different fields and academic contexts. Extending well beyond the project's base in Florence, Italy, workshops were organized in northeastern Turkey, Germany, Croatia, and Bosnia Herzegovina, and summer schools were held in Italy, Tunisia, Spain, Morocco, and Uzbekistan (Fig. 1).